A needs analysis and training considerations for female adolescent basketball players - Andreyo, E.; Unverzagt, C.; Tompkins, J.; Dawes, J. J.; Croll, S. (Strength and Conditioning Journal, 2024)
Basketball is a multidirectional sport that holds unique and multifaceted physiologic demands. Strength and conditioning professionals should consider addressing sports performance and injury mitigation in basketball using a thorough needs analysis. However, one must acknowledge that not all basketball athletes are the same. Specifically, school-aged female basketball players sustain injuries at a significantly higher rate than their male counterparts, particularly at the knee and ankle. Adolescent females also have unique maturational characteristics and concerns. Consequently, it is reasonable to surmise that female adolescent basketball players have unique strength and conditioning needs to be considered when designing training programs to improve performance and mitigate injury. Currently, there is limited peer-reviewed literature to aid strength and conditioning practitioners working with this population. The purpose of this paper is to review the unique attributes and needs of adolescent female basketball players while offering practical guidance in testing and assessment, strength training, conditioning, and injury mitigation for their sport.